Cost rationalizing actions in the spare parts production process – opinion of experts from the machinery sector - Nogalski, Bogdan; Niewiadomski, Przemysław (Research Papers of Wrocław University of Economics, 2018)
The publication describes research aimed at answering the question: which actions rationalize the costs in the production process of spare parts for agricultural machines as well as which of the mentioned actions and to which extent should be taken by Polish manufacturing companies operating in the sector subject to the research? The article is composed of two parts, i.e. theoretical-design and empirical. Using the method of reconstruction and interpretation of the subject literature – supported by experience, participatory observation as well as creative discussion among intentionally selected experts – under the first part – a catalog has been defined of postulated actions significantly rationalizing spare parts production costs. In the empirical scope (the second part of the publication), the intention of the authors was to determine the degree to which the defined actions should be taken by the companies subjected to the study
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 37-51
Keywords: production costs; cost rationalization; agricultural machines sector; koszty produkcji; racjonalizacja kosztów; sektor maszyn rolniczych